PENSEJARAHAN MELAYU-JOHOR, SEHINGGA AWAL ABAD KE-20, TINJAUAN SEPINTAS LALU - Nordin, Mardiana (SEJARAH: Journal of the Department of History, 2017)
Based on Malay historical manuscripts, this article studies the political development of Johor from the seventeenth century until the twentieth century.